2013
DOI: 10.4103/2278-9626.112325
|View full text |Cite
|
Sign up to set email alerts
|

Maxillary ameloblastoma extending into the maxillary sinus

Abstract: Ameloblastoma is a benign but locally aggressive odontogenic tumor. Worldwide, maxillary ameloblastoma is rare, but its late detection renders adequate treatment difficult. Majority occur in the mandible with about 5-20% occurring in the maxillary bone. Here we report a case of plexiform ameloblastoma of the left maxilla in a 30-year-old male. The tumor was presented as a radiographically solid mass filling the left maxillary sinus and clinically as a maxillary swelling. The radio-pathological features of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our study is consistent with the result of literature review which reported that radicular cysts are most common odontogenic jaw cyst and constitute more than 50% of jaw cysts and maxillary ameloblastoma accounting for 9-10% of all odontogenic tumors. 2,12 Dermoid cyst and sebaceous cyst are considered rare lesion in nasomaxillary area. Inverted papilloma is a neoplasm that is histopathologically benign but clinically malignant lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is consistent with the result of literature review which reported that radicular cysts are most common odontogenic jaw cyst and constitute more than 50% of jaw cysts and maxillary ameloblastoma accounting for 9-10% of all odontogenic tumors. 2,12 Dermoid cyst and sebaceous cyst are considered rare lesion in nasomaxillary area. Inverted papilloma is a neoplasm that is histopathologically benign but clinically malignant lesion.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that only 20% of ameloblastomas occur in the maxilla, although some reports indicate an incidence as low as 1% in the maxilla and of those 47% occur in the molar region, 15% in the antrum and the floor of the nose, 9% in the premolar areas, 9% in the canine regions and 2% in the palate. 8 Ameloblastoma occurs over a broad age range; cases have been reported in children younger than 10 years through elderly adults older than 90. The average age at diagnosis consistently is reported in the age range of 33 to 39, and most cases cluster between ages 20 and 60 years, 9 as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes, invasive maxillary ameloblastomas with extension into the orbit, frontal sinus, skull base, middle cranial fossa and petrous apex have resulted in the death of the patient. 8 Patients with ameloblastoma most commonly present with chief complaints of swelling and facial asymmetry. Although, the swelling is typically asymptomatic, pain is an occasional presenting sign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation